Implementasi Akuntabilitas di Sekolah Dasar - Firda Fitrotul Unsa; Tiara Haroen; Wanda Zahratul Mustafafi; Arumia Fairuz Husna; Luthfia Amanda Sari; Indra Lesmana; Ahmad Furqon Akhbar (Universitas Negeri Malang, 2023)
Abstract: In the world of education, school accountability is usually indirectly related to the use of processes from school management that are able to be held accountable. Accountability within the scope of educational institutions has meaning in giving responsibility for the process of organizing and implementing the mission and functions of education. This study aims to describe how elementary school accountability is implemented through 5 aspects, namely graduate quality, learning process, teacher quality, school management, standard fulfillment, especially in Gadang 3 Public Elementary School, Malang City. The approach used by researchers is qualitative research by conducting direct interviews with informants and literature studies by collecting various data related to the topics studied through various sources, journals, articles, laws and regulations, and other literary sources related to the implementation of program evaluation education against national education standards. The method used is direct interviews with informants regarding each aspect of accountability. The results found were (1) the quality of graduates at SD Negeri Gadang 3 Malang City fulfilled about 78 percent of all indicators, (2) the learning process fulfilled about 94 percent of all indicators, (3) aspects of teacher quality fulfilled all indicators of accountability, (4 ) aspects of school management get 95 percent of the achievement indicators, and (5) fulfillment of standards by this school get 86 percent of the total indicators.Keywords: implementation; accountability; elementary schoolAbstrak: Pada dunia pendidikan biasanya akuntabilitas sekolah secara tidak langsung akan berkaitan dengan penggunaan proses dari manajemen sekolah yang mampu untuk dipertanggung jawabkan. Akuntabilitas pada lingkup instansi pendidikan memiliki arti dalam memberikan tanggung jawab atas proses penyelenggaraan dan pelaksanaan misi serta fungsi pendidikan. Penelitian ini ditujukan untuk mendeskripsikan bagaimana pengimplementasian akuntabilitas sekolah dasar melalui 5 aspek yakni mutu lulusan, proses pembelajaran, mutu guru, manajemen sekolah, pemenuhan standar khususnya di SD Negeri Gadang 3 Kota Malang. Pendekatan yang digunakan peneliti yaitu penelitian kualitatif dengan melakukan wawancara secara langsung dengan narasumber dan studi literatur dengan mengumpulkan berbagai data yang berhubungan dengan topik yang dikaji melalui berbagai sumber, jurnal, artikel, peraturan perundang-undangan, dan sumber pustaka lainnya yang berkaitan dengan pelaksanaan evaluasi program pendidikan terhadap standar nasional pendidikan. Metode yang digunakan ialah wawancara langsung bersama informan terkait masing-masing aspek akuntabilitas. Hasil yang ditemukan ialah (1) mutu lulusan di SD Negeri Gadang 3 Kota Malang memenuhi sekitar 78 persen dari keseluruhan indikator, (2) proses pembelajaran memenuhi sekitar 94 persen dari keseluruhan indikator, (3) aspek mutu guru memenuhi keseluruhan indikator akuntabilitas, (4) aspek manajemen sekolah mendapatkan 95 persen dari hasil capaian indikator, dan (5) pemenuhan standar oleh sekolah ini diperoleh 86 persen dari keseluruhan indikator.Kata kunci: implementasi; akuntabilitas; sekolah dasar